Pengaruh Penggunaan Media Sosial Facebook terhadap Peningkatan Penjualan Komoditas Hortikultura di Kota Serang - Retno Pratiwi; Dwi Anisa Andriyani; Aliudin Aliudin; Mey Puspita Dewi Manullang; Arindra Siwi Damaiyanti (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This study is intended to examine the marketing strategies implemented by horticultural farmers in Serang City by utilizing the Facebook platform, and to find out whether the number of posts and comments can affect sales volume. This study applies a quantitative approach with multiple regression analysis techniques. Data was collected by purposive sampling method through interviews, questionnaires and observations by horticultural farmers in the Facebook community “Petani Serang Banten”, with the number of samples used as many as 9 horticultural farmers. The results of this study show that there is an influence between the independent variables (number of posts and number of comments) on the dependent variable (the level of sales of horticultural commodities). In this study, horticultural farmers are advised to be able to utilize Facebook social media in marketing their agricultural products.